EFFECTS OF ETHICAL ACCOUNTING PRACTICES ON FINANCIAL REPORTING: A SURVEY OF LISTED FIRMS IN KENYA - Kukutia, Douglas Paul; Gathii, John Kamau; Gitahi, Samson Njenga (International Journal of Business Management and Processes, 2019)
Listed companies attract mutual and hedge funds, institutional and market traders due to the indirect advertising and endorsement in most major exchanges. For these companies to continue attracting investors, they have to provide financial reports to the public as well as shareholders. Through Institute of Certified Public Accountants of Kenya, accounting and finance practitioners have promoted the implementation of International Public Sector Accounting Standards (IPSAS). Despite the efforts, listed firms in the country continue to face challenges in financial reporting. This study thus sought to investigate the effects of ethical accounting practices on financial reporting of listed firms in Kenya. It specifically examined the effects of accounting objectivity, professional competence, integrity and confidentiality on listed firms in Kenya. The study adopted a descriptive research design and all the 67 listed firms in Kenya were targeted. The study used census method to select all the listed companies. However, six (10%) listed firms were selected for a pilot study and the other 61 firms were studied in the actual study. Structured questionnaires were used in data collection. The reliability of the instruments was tested using Cronbach’s Alpha test of internal consistency and found to be adequate at 0.7. Data analysis was done using Statistical Package for Social Sciences (SPSS) where descriptive statistics (frequencies, percentages and mean scores) and inferential statistics (Pearson Correlations and simple linear regressions) were employed. A multiple linear regression analysis was also employed with a view of explaining the influence of objectivity, professional competence, integrity and confidentiality on the financial reporting of the listed firms. The study found a coefficient of determination of 0.632 indicating that 63.2% of the variability in the financial reporting is attributable to the cumulative effect of confidentiality, professional competence, objectivity, and integrity. The achieved beta coefficients for objectivity, professional competence, integrity and confidentiality had beta coefficients of 0.264, 0.263, 0.299, and 0.228 respectively. The positive beta coefficients of all the variables indicated that increases in the respective independent variables were associated with increases in the dependent variable with the remainders of the variables kept constant. The study further found that there were statistically significant relationships between each of the accounting practices and financial reporting.
FULL TEXT
Keywords: Financial Reporting, Ethical Accounting Practices, Accounting Objectivity, Professional Competence, Integrity and Confidentiality